Gamification in Higher Education: A Systematic Literature Review with Particular Reference to Octalysis as the Futuristic Framework for Further Research - Rao, Harika (Journal for leadership and instruction, 2022)
An educator's goal has always been to achieve higher student success in learning outcomes. Making students interested in learning is one of the critical factors in achieving that goal. During the past decade, 'gamification' has become a buzzword in business, medical and educational fields that has attracted many researchers. Though there are many definitions of "gamification" in use, for this study, the definition of Educause will be adopted: "Gamification is the application of game elements in non-gaming situations, often to motivate or influence behavior" (Educause, 2011). This literature review explores the dynamic improvements in gamification in higher education and the feasibility of enhancing the student's motivation and engagement with the learning process by dwelling more on the behavioral aspects of motivation.